Update on Rehabilitation Strategies for Swimmers' Shoulder: A Narrative Review - Dcosta, Selena; Nair, Aishwarya (Journal of Health and Allied Sciences NU, 2024)
Swimmers' shoulder is one of the common overuse injuries having multifactorial causes with a gradual onset. Swimmers' experience pain in the pull-through phase, during the mid-stroke wherein the arm is maximally internally rotated and adducted. This occurs due to a significant amount of force generated by the pectorals, latissimus dorsi, subscapularis, serratus anterior, rhomboids, and supraspinatus for this movement. The repetitive use of shoulder muscles during the swim strokes predisposes it to overuse injuries among which shoulder impingement is common. It hinders participation of athletes in competitive events and reduces the efficiency of the swim performance. This review aims to provide a consolidated overview and identify various rehabilitation strategies and exercise programs for swimmers' shoulder. A thorough search was done on PubMed, ScienceDirect, Web of Science, Cochrane, CINAHL, and Clinical Key to find relevant articles in relation to the rehabilitation strategies available for swimmers' shoulder. Overall, this review suggests that aquatic concentric-eccentric exercise, Kinesio taping, land-based strengthening exercises, and rhythmic stabilization exercises significantly improve pain and functional activity in individuals with swimmers' shoulder.
Keywords: swimmers' shoulder; shoulder impingement syndrome; shoulder pain; rehabilitation